Student Worksheets Based on HOTS in Elementary School - Dewi Sri Lestari; Intan Rahmawati; Diana Endah Handayani (Indonesian Journal Of Educational Research and Review, 2021)
The Importance of HOTS-Based Student Worksheets in Elementary Schools. High Order Thinking Skill (HOTS) in elementary schools can increase students' higher-order thinking skills. The purpose of this study was to analyze the high-grade HOTS-based Student Worksheets in Elementary Schools. This type of research is descriptive qualitative research. The method used to collect data are interviews, observation, and documentation. The instrument used to collect data is a questionnaire. The research subject is the fourth-grade teacher. The technique used to analyze the data is descriptive qualitative and quantitative analysis. This study indicates that the analysis of the high-grade HOTS-based Student Worksheets in elementary schools has been implemented by the teacher quite well. The Student Worksheets made by the teacher have led to higher-order thinking skills, namely C4 (analyzing), C5 (evaluating), and C6 (creating), according to the results of interviews and documentation data. It can be concluded that the analysis of the HOTS-based student worksheets has been realized well. Suggestions that can be given are to re-emphasize High order thinking skills (HOTS) into Student Worksheets so that learning can be maximized in applying HOTS.